THE IMPLEMENTATION OF EMAIL EXCHANGE AS PART OF BLENDED LEARNING IN EFL WRITING CLASS : A Case Study between Indonesian and American Classrooms on ePals Project - Afiani, Astuti (2014)
This study presents data from qualitative case study investigating the writing improvement of 10th grade EFL students through blended learning in Indonesia. The blended learning was incorporated in the email exchange through ePals project for six-week teaching program between EFL students in Indonesia and students in the USA. This study employed classroom practices from blended learning; however this study can also be considered as synthesis from several theories including process writing, constructivism and Systemic Functional Grammar (Halliday, 1994, Eggins, 1994) for the text analysis. During the teaching program, the interactions in the blended learning took place both online and face-to-face. The EFL students wrote four interactive emails to their partners as their online interaction and had a class discussion as their face-to-face interaction. The observation was carried out to identify how the EFL students get their writing improvement. The students' emails were also collected for analysis using transitivity and mood in SFG framework.After the teaching program, the students were asked through questionnaires for their responses on the teaching program. There were some significant improvements on EFL students' writing. The EFL students systematically studied the vocabularies and grammatical structure from the incoming emails and class discussion to improve their next emails. The linguistic features allow the students to bridge their expression from oral expression to written expression. The students' responses were positive and they said they made improvement in their writing because they got more confident in writing. However, some technical problems were unavoidable due to the nature and challenges in blended learning. Keywords: Blended learning, ePals project, Online interaction, Face-to-face interaction